Relevance of Crop Biology for Environmental Risk Assessment of Genetically Modified Crops in Africa - Akinbo, Olalekan; Hancock, James F.; Makinde, Diran (Frontiers in Bioengineering and Biotechnology, 2015)
Knowledge about the crop biology of economic crops in Africa is needed for regulators to accurately review dossiers and conduct comprehensive environmental risk assessments (ERA). This information allows regulators to decide whether biotech crops present a risk to biodiversity, since crossing between domesticated crops and their wild relatives could affect the adaptations of the wild species. The criteria that should be used in the evaluation of African crops for environmental risk assessment (ERA) include: growth habit, centre of origin, centre of genetic diversity, proximity of wild relatives, inter-fertility, mode of pollen dispersal, length of pollen viability, mating system, invasiveness, weediness, mode of propagation, mode of seed dispersal and length of seed dormancy. In this paper, we discuss the crops being genetic engineered in Africa and describe the crop biology of those with native relatives.